2019
DOI: 10.1371/journal.pcbi.1007024
|View full text |Cite
|
Sign up to set email alerts
|

Predicting three-dimensional genome organization with chromatin states

Abstract: We introduce a computational model to simulate chromatin structure and dynamics. Starting from one-dimensional genomics and epigenomics data that are available for hundreds of cell types, this model enables de novo prediction of chromatin structures at five-kilo-base resolution. Simulated chromatin structures recapitulate known features of genome organization, including the formation of chromatin loops, topologically associating domains (TADs) and compartments, and are in quantitative ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 99 publications
5
76
0
Order By: Relevance
“…2b) and the contact probability as a function of genomic separation averaged over all chromosomes inactive (B) chromatin. 4,38 However, we found that these finer structures were not necessary for an accurate modeling of chromosome positioning and inter-chromosomal interactions, indicating that sub-compartments might only contribute to local chromatin folding rather than global genome organization.…”
Section: Simulated Contact Map Reproduces Experimental Hi-c Datamentioning
confidence: 87%
See 3 more Smart Citations
“…2b) and the contact probability as a function of genomic separation averaged over all chromosomes inactive (B) chromatin. 4,38 However, we found that these finer structures were not necessary for an accurate modeling of chromosome positioning and inter-chromosomal interactions, indicating that sub-compartments might only contribute to local chromatin folding rather than global genome organization.…”
Section: Simulated Contact Map Reproduces Experimental Hi-c Datamentioning
confidence: 87%
“…While the polymer model is motivated to recapitulate various biological mechanisms of genome organization, it is also data-driven and all of its parameters can be determined from haploid Hi-C data with an iterative optimization algorithm. 27,38 Model parameterization is possible because mathematical expressions for the various energy terms in U Genome (r) were designed such that their ensemble averages can be mapped onto combinations of contact frequencies measured in Hi-C. As shown in Fig. 1, we first perform molecular dynamics simulations to collect an ensemble of genome structures.…”
Section: A Data-driven Mechanistic Model For the Diploid Human Genomementioning
confidence: 99%
See 2 more Smart Citations
“…Advances in resolving three-dimensional chromatin structure and how it varies (Kishi & Gotoh, 2018;Marti-Renom et al, 2018;Qi & Zhang, 2019) hold long term hope for progress here. Figure 1: Workflow of the method for identification of probable causative variants.…”
Section: Scope For Improvementmentioning
confidence: 99%